2018
DOI: 10.18203/issn.2454-5929.ijohns20180504
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of pediatric neck masses

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">Pediatric neck masses are a reason for anxiety for both patients and doctor as there can be chances of malignancy. There are few established guidelines for evaluation. The etiology is varied so a thorough knowledge of clinical presentation is essential. </span></p><p class="abstract"><strong>Methods:</strong> <span lang="EN-IN">A clinicopathological analysis of 150 cases of neck masse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…In current study, fever (52%) is the most common associated presenting complaint. Similar findings were [13][14][15] Studies among paediatric neck masses done by Showkat et al, Govari et al, Deeva et al, Cannolly et al and Gangwar et al found that reactive lymphadenopathy is the most common infective neck swelling. 2,13,[16][17][18] Similar findings noted in current study 46% (N=47) are reactive lymphadenitis cases.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In current study, fever (52%) is the most common associated presenting complaint. Similar findings were [13][14][15] Studies among paediatric neck masses done by Showkat et al, Govari et al, Deeva et al, Cannolly et al and Gangwar et al found that reactive lymphadenopathy is the most common infective neck swelling. 2,13,[16][17][18] Similar findings noted in current study 46% (N=47) are reactive lymphadenitis cases.…”
Section: Discussionsupporting
confidence: 77%
“…In our study the symptomatology of fever, local pain and dysphagia (p<0.05), need for institutional management (p=0.001) with respect to deep neck space infection is statistically significant when associated with submandibular space, Similar to the study carried by Gangwar et al who found the submandibular space to be involved commonly. 13 One case of submandibular space infection had spread of infection to parapharyngeal and retropharyngeal space which was managed surgically. In current study the lateral or midline infective neck swellings on treatment, improved clinically irrespective of the modality (p<0.02) ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Benign lesions are usually more common in younger age from 11 to 20 years as nasopharyngeal angiofibroma was more common in adult age in our study. As per Aloke Bose Majumdar et al, non-neoplastic nasal masses were the commonest in the 2nd to 4th decade of life [6].…”
Section: Discussionmentioning
confidence: 87%